(untitled) (UNIZIK Journal of STM Education, 2025)
The study investigated the relationship between parental attitude and parental involvement on students’ interest and academic achievement in biology in Aguata Education Zone. The design for the study was correlational survey design. Two research questions and two hypotheses were used for the study. The research was done in Aguata Education Zone in Anambra state. The population consisted of 2,072 (926 males and 1,146 females) Senior Secondary II students from all the 52 public secondary schools in Aguata Education Zone of Anambra state. The sample for the study consisted of 400 SS II Biology students obtained through multi stage sampling procedure. Three instruments titled Parental Attitude towards Biology Questionnaire (PATBQ), Parental Involvement in Biology Questionnaire (PIBQ) and Academic interest scale (AIS) were the instrument used for data collection. These instruments were validated and tested for reliability with reliability coefficient being .969, .981 and 0.981 for PATBQ, PIBQ and AIS respectively using Cronbach Alpha method. Students result for 2023/2024 academic session was also used as academic achievement scores for the study. The research questions were answered using Pearson Product Moment Correlation Coefficient while the hypotheses were tested at 0.05 level of significance using Simple linear regression. The findings of the study showed significant relationship between parental attitude and parental involvement on students’ interest and academic achievement in biology in Aguata Education zone. This implies that parental attitude and parental involvement are capable of enhancing academic achievement and interest in Biology. It was recommended among others that parental attitude and involvement should be improved through academic seminars and workshop towards students’ interest especially in Biology in senior secondary schools.